K определению основных стилеобразующих элементов (на материале исследований в германистике) - Исаев, Э.Ш. (Культура народов Причерноморья, 2013)
Статья посвящена анализу современных подходов к определению понятия «стиль» с точки зрения современной германистики. В широком смысле понятие "стиль" используется для идентификации конкретного поведения, творческого процесса или направления в искусстве. Подчеркивается особая роль исследования факультативных элементов стилеобразования на разных уровнях языковой системы. Определяются наиболее весомые факультативные элементы на лексическом, грамматическом и фонетическом уровнях. Ключевые слова: стиль, речь, факультативный элемент, понимание. Статтю присвячено аналізу сучасних підходів до визначення поняття «стиль» з точки зору сучасної германістики. В загальному плані поняття «стиль» використовується для ідентифікації конкретної поведінки, творчого процесу або напряму в мистецтві. Підкреслюється особлива роль дослідження факультативних елементів стильотворення на різних рівнях мовної системи. Визначаються найбільш вагомі факультативні елементи на лексичному, граматичному та фонетичному рівнях. Ключові слова: стиль, мовлення, факультативний елемент, розуміння. The article analyzes the current approaches to the definition of "style" from the point of view of modern German Studies. The concept of "style" is used to wide extent to identify a specific behavior, the nature of the creative process or trend in art. The analysis of linguistic characteristics that could be relevant to the description of the “style” notion is carried out. The special role of the research of style formation optional elements at different levels of the language system is emphasized. The author of the utterance has different linguistic resources to express his thoughts. The following factors effect the author’s preferences: the language system resources, the subject of the utterance, the purpose of the utterance, the speaker's personality, the listener’s personality, the situation of communication. Language features are optional elements of the text, the appropriate statement style is presented by means of them. Optional elements are complex hierarchically organized system of variant elements, which are interdependent with obligatory means of expression. The most significant optional elements at the lexical, grammatical and phonetic levels are identified. Key words: style, speech, optional element, comprehension.